2021
DOI: 10.3390/foods10112817
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Characterization of Unrefined Durum Wheat Air-Classified Fractions

Abstract: Durum wheat milling is a key process step to improve the quality and safety of final products. The aim of this study was to characterize three bran-enriched milling fractions (i.e., F250, G230 and G250), obtained from three durum wheat grain samples, by using an innovative micronization and air-classification technology. Milling fractions were characterized for main standard quality parameters and for alveographic properties, starch composition and content, phenolic acids, antioxidant activity and ATIs. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
5
6
0
Order By: Relevance
“…Conversely, the presence of toxins was not detected in semolina. This result is consistent with previous studies showing the greater difficulty of managing toxin-producing fungi (i.e., F. langsethiae) colonising the inner endosperm of the kernel and thus strongly limiting semolina contamination [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Interestingly, the toxin content (sum of T-2 and HT-2) tended to concentrate in the F250 fraction, and a higher bran content was clearly demonstrated by the measurement that was close to the limit of quantification of the ELISA test (25 µg/g).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, the presence of toxins was not detected in semolina. This result is consistent with previous studies showing the greater difficulty of managing toxin-producing fungi (i.e., F. langsethiae) colonising the inner endosperm of the kernel and thus strongly limiting semolina contamination [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Interestingly, the toxin content (sum of T-2 and HT-2) tended to concentrate in the F250 fraction, and a higher bran content was clearly demonstrated by the measurement that was close to the limit of quantification of the ELISA test (25 µg/g).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the latter effect was evident as the progressive airflow opening increased. In addition, based on the contamination rates observed, the three air-classified fractions (F250, G250, and G230), previously selected based on qualitative evaluation, were confirmed as suitable products for the pasta-making process [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…‘Red’). As previously reported [ 50 ], the highest antioxidant capacity was observed in whole grains, which contain more bioactive compounds of health interest, such as insoluble fiber, phenolic acids, and alkylresorcinols [ 51 ].…”
Section: Resultssupporting
confidence: 58%
“…The antioxidant capacity, total phenolic content (TPC) and anthocyanin content from the free and bound phenolic extracts are reported in Table 7. Previous research reported in the literature has shown that phenolics and antioxidant compounds fractionate differently between air-classified coarse and fine fractions (Cammerata et al, 2021;Inglett & Chen, 2011). These compounds impart a range of potential health benefits to pulses and pulse-based products, including reduced inflammation (Milesi et al, 2022) and lowering the risk of developing cardiovascular disease (Rangel-Huerta et al, 2015) and diabetes (Charoensiddhi et al, 2022).…”
Section: Phytochemical Analysis Of Pulse Flours and Air-classified Fr...mentioning
confidence: 99%